Mir-509-5p joins the Mdm2/p53 feedback loop and regulates cancer cell growth - Ren, Z-J (Cell Death Dis, 2014)
Although the Mdm2/p53 interaction has been well documented, it is not clear whether there are new microRNAs participating in this regulatory network. Here, we provide evidence that miR-509-5p, which is downregulated in a subset of newly diagnosed cervical cancer and hepatocellular carcinoma tissues compared with the adjacent nontumor tissue, can be activated by p53 through binding the promoter of miR-509-5p and it suppresses the growth and invasion/migration of cervical cancer and hepatoma cells by regulating apoptosis and the G1/S-phase transition of cell cycle. Furthermore, Mdm2 was identified to be a target of miR-509-5p by targeting its 3′-UTR. Restoration of Mdm2 abrogated the cell phenotypes induced by miR-509-5p. Moreover, ectopic expression of miR-509-5p in HeLa and QGY-7703 cells repressed the expression of Mdm2, subsequently enhancing its p53-activating effects. These results suggest that miR-509-5p is a new regulator of Mdm2/p53 pathway and may play a key role in cancer development.